2016
DOI: 10.1016/j.metabol.2015.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic association of elevated serum free fatty acid and glucose levels with large arterial stiffness in a general population: The Nagahama Study

Abstract: Physiological variations in FFA concentrations might be a risk factor for large arterial stiffness. FFA and hyperglycemia exert a synergistic adverse effect on the vasculature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…48,49 Elevated fasting FFAs are associated with brachial arterial stiffness measured by pulse wave velocity and with an increased risk incident of cardiac failure. 50,51 FFAs during hyperinsulinemia also correlated well with coronary artery calcification in adults with type 1 diabetes. 52 Chronic daytime elevations of FFAs in girls with PCOS could lead to increased vascular-specific inflammatory markers and the development of arterial stiffening and thickening of the intimal and medial layers of the arterial wall.…”
Section: Discussionmentioning
confidence: 75%
“…48,49 Elevated fasting FFAs are associated with brachial arterial stiffness measured by pulse wave velocity and with an increased risk incident of cardiac failure. 50,51 FFAs during hyperinsulinemia also correlated well with coronary artery calcification in adults with type 1 diabetes. 52 Chronic daytime elevations of FFAs in girls with PCOS could lead to increased vascular-specific inflammatory markers and the development of arterial stiffening and thickening of the intimal and medial layers of the arterial wall.…”
Section: Discussionmentioning
confidence: 75%
“…In this cross-sectional study of 9396 Japanese subjects, Tabara et al [56] showed an association between elevated serum free fatty acids levels and large arterial stiffness, measured through brachial-to-ankle pulse wave velocity (baPWV) in a large-scale epidemiological setting. Individuals were subdivided according to clinical characteristics and fasting status.…”
Section: Non-interventional Clinical Research Studiesmentioning
confidence: 99%
“…Many studies reported that arterial stiffness increases with age, 9 hypertension, 10 obesity, 11,12 smoking, 13 diastolic heart failure, 14 diabetes, 15 coronary artery disease, 16 peripheral arterial disease, 17 dyslipidemia, 18 and end-stage renal disease. 19 …”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Other predictors include central pulse pressure (CPP) and augmentation index (AI), usually found elevated in patients with end-stage renal disease, and constitute strong independent predictors of all-cause mortality including cardiovascular mortality. [5][6][7][8] Many studies reported that arterial stiffness increases with age, 9 hypertension, 10 obesity, 11,12 smoking, 13 diastolic heart failure, 14 diabetes, 15 coronary artery disease, 16 peripheral arterial disease, 17 dyslipidemia, 18 and end-stage renal disease. 19 While many studies explored the relation of age to PWV and various sphygmocardiographic parameters, few have focused on the relations between the PWV and biochemical parameters.…”
Section: Introductionmentioning
confidence: 99%